Influence of Al and Cu Doping on the Structure, Morphology, and Optical Properties of ZnO Thin Film - Arif Tjahjono; Aga Ridhova; Pramitha Yuniar Diah Maulida; Alfian Noviyanto; Didik Aryanto; Faras Afifah (Indonesian Journal of Chemistry, 2023)
In this study, ZnO thin films doped with Al (AZO) and Cu (CZO) were fabricated on a glass substrate via sol-gel spin coating. The influence of 1 atomic % Al and Cu doping on the structure, morphology, as well as optical properties of ZnO thin film was then analyzed with X-ray diffraction (XRD), atomic force microscopy (AFM), and UV-Vis spectroscopy. XRD analysis revealed that all samples possessed hexagonal wurtzite crystal structures with 3 to 4 preferred orientations. Al and Cu doping caused a decrease in crystal size, while the lattice strain (e) and dislocation density (ρ) were increased. AFM indicated that Al and Cu doping reduced the surface roughness of the ZnO thin film. Optical measurement showed that all samples exhibited high transmittance (> 80%) in the visible light region. Transmittance was reduced after doping, while the band gaps for ZnO, AZO, and CZO thin films are 3.26, 3.28, and 3.23 eV. This study showed that an addition of 1 atomic % transition metal (Al and Cu) greatly influences the structure, morphology, and optical properties of ZnO thin film.